Why do bank customers switch? A systematic literature review - Ngau, Christine M.; Zins, Andreas; Rengasamy, Dhanuskodi (2023)
Purpose: The digital transformation in the banking industry has brought about complexity and competitiveness which has made differentiation challenging for banks. Complemented by consumer empowerment through high accessibility of information on the internet, this has led to a phenomenon known as switching behavior. The purpose of this review is to examine the determinants governing switching behavior among bank customers. This review highlights the importance of research which looks beyond pre-adoption behavior by examining post-adoption behavior; what happens after initial technology acceptance. Design/methodology/approach: This review examines 44 journal articles researching switching behavior published between 1995 and 2022 in top journals. From a synthesis of literature, a conceptual framework for analysis and understanding switching behavior is presented. Findings: Although various scholars have investigated switching behavior among bank customers, there are few studies which provide a comprehensive review and research classifications in this area. This review classifies key determinants of switching behavior into socio-demographic factors, situational triggers, influential triggers and reactional triggers. Structural equation modelling is the most common research methodology utilized in reviewed articles. The literature review reveals that mediators and moderators are less commonly deployed compared to determinants. Findings also indicate switching behavior studies still lack theory-driven conceptual frameworks. Originality/value: This paper is the first systematic literature review on switching behavior research among bank customers spanning across 28 years in top academic journals. It integrates insights from 44 relevant research papers through publication trends. This review identifies key research gaps and provides future research directions.